A live‐attenuated pneumococcal vaccine elicits CD4+ T‐cell dependent class switching and provides serotype independent protection against acute otitis media. Issue 1 (4th November 2013) - Rosch, Jason W; Iverson, Amy R; Humann, Jessica; Mann, Beth; Gao, Geli; Vogel, Peter; Mina, Michael; Murrah, Kyle A; Perez, Antonia C; Edward Swords, W; Tuomanen, Elaine I; McCullers, Jonathan A
Abstract Acute otitis media (AOM) caused by Streptococcus pneumoniae remains one of the most common infectious diseases worldwide despite widespread vaccination. A major limitation of the currently licensed pneumococcal vaccines is the lack of efficacy against mucosal disease manifestations such as AOM, acute bacterial sinusitis and pneumonia. We sought to generate a novel class of live vaccines that (1) retain all major antigenic virulence proteins yet are fully attenuated and (2) protect against otitis media. A live vaccine candidate based on deletion of the signal recognition pathway component ftsY induced potent, serotype‐independent protection against otitis media, sinusitis, pneumonia and invasive pneumococcal disease. Protection was maintained in animals coinfected with influenza virus, but was lost if mice were depleted of CD4+ T cells at the time of vaccination. The live vaccine induced a strong serum IgG2a and IgG2b response that correlated with CD4+ T‐cell mediated class switching. Deletion of genes required for microbial adaptation to the host environment is a novel live attenuated vaccine strategy yielding the first experimental vaccine effective against pneumococcal otitis media.